New Hampshire Field Studies of Membrane Encapsulated Soil Layers with Additives. - Eaton,Robert A; Berg,Richard L (1980)
This report describes the construction, instrumentation, and performance of membrane encapsulated soil layer (MESL) pavement test sections at the U.S. Army Cold Regions Research and Engineering Laboratory in Hanover, New Hampshire, from 1973 to 1978. Membrane encapsulated soil layer construction involves using a waterproof membrane to protect low grade soils from absorbing moisture, especially during the freezing process. Most of these lower grade soils are frost-susceptible; in these soils water can be drawn to the freezing zone to form ice lenses, which in turn cause heaving of the surface. Lime, flyash, and sodium chloride were added to silt material prior to encapsulation. These additives were incorporated to add strength to the silt, absorb excess moisture, and increase its load-supporting capabilities. Results show that (1) the moisture content within the MESL sections remained relatively constant over the five years of testing; (2) a nonencapsulated lime-flyash-stabilized silt material heaved 8.8 times as much as the identical material which was encapsulated; (3) the lime-flyash-stabilized MESL had twice the strength of the plain or salt-stabilized MESL; (4) the silt with the additives had less frost heave within the MESL than the untreated silt. In summary, MESL's can be constructed to perform well in cold regions, thereby replacing high quality aggregates which are being depleted. (Author)